2024
DOI: 10.5194/isprs-annals-x-1-2024-67-2024
|View full text |Cite
|
Sign up to set email alerts
|

Comparing Deep Learning and MCWST Approaches for Individual Tree Crown Segmentation

Wen Fan,
Jiaojiao Tian,
Jonas Troles
et al.

Abstract: Abstract. Accurate segmentation of individual tree crowns (ITC) segmentation is essential for investigating tree-level based growth trends and assessing tree vitality. ITC segmentation using remote sensing data faces challenges due to crown heterogeneity, overlapping crowns and data quality. Currently, both classical and deep learning methods have been employed for crown detection and segmentation. However, the effectiveness of deep learning based approaches is limited by the need for high-quality annotated da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…The widespread, successful use of these models in this domain is summarized by different overview papers and systematical literature reviews, such as Kattenborn et al [11] and Zhao et al [23]. Furthermore, Fan et al [24] showed that deep learning approaches outperform statistical segmentation approaches such as marker-controlled watershed transformation (MCWST).…”
Section: Supervised Deep Learning On Forest Datasetsmentioning
confidence: 99%
“…The widespread, successful use of these models in this domain is summarized by different overview papers and systematical literature reviews, such as Kattenborn et al [11] and Zhao et al [23]. Furthermore, Fan et al [24] showed that deep learning approaches outperform statistical segmentation approaches such as marker-controlled watershed transformation (MCWST).…”
Section: Supervised Deep Learning On Forest Datasetsmentioning
confidence: 99%